Cover Feature: Selective Hydrogenolysis of Erythritol over Ir−ReOx/Rutile‐TiO2 Catalyst (ChemSusChem 2/2021). Issue 2 (22nd December 2020) - Gu, Minyan; Liu, Lujie; Nakagawa, Yoshinao; Li, Congcong; Tamura, Masazumi; Shen, Zheng; Zhou, Xuefei; Zhang, Yalei; Tomishige, Keiichi
Abstract : The Cover Feature shows the catalytic selective production of 1, 4‐butanediol from erythritol, which is a C4 biomass‐derived platform molecule. High concentration of loaded rhenium‐oxide‐modified iridium particles on the support surface increases the production rate of 1, 4‐butanediol. More information can be found in the Full Paper by M. Gu, L. Liu, et al .